Peningkatan Keterampilan Menulis Geguritan dengan Metode 3M pada Siswa Kelas IX SMP Negeri 3 Kroya (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Learning to write geguritan is one of the materials that are difficult for students to master. Limited diction, students' disinterest in learning literature, teachers who are less creative in learning, and students' difficulties in getting ideas are the main factors of student difficulties. Knowing these problems, the researchers are trying to improve students' skills in writing geguritan using the 3M learning method using short film media. The researcher used the penelitian tindakan kelas (PTK) method with 32 students in class IX B, SMP Negeri Kroya, as the subject. PTK is carried out in two cycles, which produce data based on test and non-test instruments. The data analysis technique used is quantitative and qualitative. In the pre-cycle action, the average value is 73, this value is in the sufficient category. Cycle 1 increased the average score to 75 in the sufficient category, but there were still 17 students whose scores were below the KKM. Observation results in cycle 1 with the target teacher showing a score of 81, while student observations get a value of 80. The average value of cycle 2 is 85 with a good category, the observations show that the teacher's score obtained is 90 with a good predicate, while students get a score of 95 or a very good predicate. Increasing students' skills in writing geguritan brings positive changes. Students become more active in asking questions to the teacher, discussing with friends, and enthusiastic in participating in learning.